2007
DOI: 10.1111/j.1399-5448.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, alcohol, and illicit drug use in adolescents with diabetes mellitus

Abstract: Compared with healthy youth, DM patients use less tobacco, alcohol, and illicit drugs during the first years of adolescence but not later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 22 publications
3
52
1
2
Order By: Relevance
“…However, several other factors such as eating disorders and depression [45], substance abuse [46], insulin omission [45], and/or weight gain, which are frequently observed during adolescence, may be related to inadequate metabolic control.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 99%
“…However, several other factors such as eating disorders and depression [45], substance abuse [46], insulin omission [45], and/or weight gain, which are frequently observed during adolescence, may be related to inadequate metabolic control.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 99%
“…For adolescents with T1DM, several studies have identified lower prevalence of alcohol and other substance use compared to the general adolescent population [7,8,17], but a more recent survey highlighted that in one clinic-based sample, more than 1 in 3 adolescents with T1DM reported past-year alcohol use and nearly 1 in 2 reported lifetime binge drinking [9]. In this same study, nearly 1 in 5 adolescents with T1DM reported past-month marijuana use.…”
Section: Epidemiology Of Substance Use Among Ycmcmentioning
confidence: 99%
“…In this same study, nearly 1 in 5 adolescents with T1DM reported past-month marijuana use. The lower prevalence of substance use reported in some studies may be due to sampling young adolescents; some data suggests that adolescents with T1DM may have lower prevalence of substance use in their early teen years but have similar prevalence to the general youth population by the end of adolescence [17]. Data from Australia highlight a high prevalence of street drug use among adolescents with T1DM, which is concerning given the appetite-altering effects of many substances with resultant effects on blood glucose levels [18,19].…”
Section: Epidemiology Of Substance Use Among Ycmcmentioning
confidence: 99%
“…One of these studies [12], which examined the secular trends in the prevalence of cigarette smoking from 1990 to 2001, showed that significant decreases in the prevalence of cigarette smoking occurred among diabetics aged ≥65 years, but not among young people with the disease. However, a relatively small number of studies, conducted in the US [15,16], Italy [17], and Chile [18], have addressed the prevalence of cigarette use behaviors among diabetic adolescents. Furthermore, hardly any study has investigated the association between cigarette smoking and diabetes status or specific characteristics of the disease, such as age at the time of diagnosis, during the transition to adulthood (AH) using longitudinal data.…”
Section: Introductionmentioning
confidence: 99%